The role of manual gestures in second language comprehension: a simultaneous interpreting experiment - Arbona, Eléonore; Seeber, Kilian G.; Gullberg, Marianne (Frontiers in Psychology, 2023)
Manual gestures and speech form a single integrated system during native language comprehension. However, it remains unclear whether this hold for second language (L2) comprehension, more specifically for simultaneous interpreting (SI), which involves comprehension in one language and simultaneous production in another. In a combined mismatch and priming paradigm, we presented Swedish speakers fluent in L2 English with multimodal stimuli in which speech was congruent or incongruent with a gesture. A picture prime was displayed before the stimuli. Participants had to decide whether the video was related to the prime, focusing either on the auditory or the visual information. Participants performed the task either during passive viewing or during SI into their L1 Swedish (order counterbalanced). Incongruent stimuli yielded longer reaction times than congruent stimuli, during both viewing and interpreting. Visual and audio targets were processed equally easily in both activities. However, in both activities incongruent speech was more disruptive for gesture processing than incongruent gesture was for speech processing. Thus, the data only partly supports the expected mutual and obligatory interaction of gesture and speech in L2 comprehension. Interestingly, there were no differences between activities suggesting that the language comprehension component in SI shares features with other (L2) comprehension tasks.